Research on the improvement of the core competitiveness of tea industry in famous tea town: A case study of Huangshan City, Anhui Province. (October 2019) - Jiang, N
Abstract: Huangshan City, Anhui Province, is one of the most suitable tea producing areas in China, with a long history of tea making. There are many varieties of tea in Huangshan, such as Maofeng, Taiping Houkui, Qimen black tea and so on. Tea industry is an important economic pillar of Huangshan City. However, statistics in recent years show that there are obvious shortcomings in the quantity and quality of tea production in Huangshan City, and the development in domestic sales and export is slow. In this paper, the diamond model proposed by Professor Michael Porter is used to analyze the competitiveness of tea industry in Huangshan City from six aspects: production factors, demand situation, related and supporting industries, enterprise strategy and structure, as well as inter-industry competition, government and opportunity. It is suggested to try to promote the operation mode of "Leading Enterprises + Production Cooperatives + Farmers + Traditional Channels + Internet +", so as to form a more complete local tea industry chain and help more local tea farmers to increase income and become rich. Furthermore, relying on the rich tourism and cultural resources in the region, this paper tries to explore a unique development path that combines tea garden experience, tea culture and local tourism, highlights local characteristics and advantages, and seeks an optimized model suitable for the development of local tea industry.